PUBLIC RESPONSE TO CELEBRITY SUICIDES NEWS DUE TO MENTAL HEALTH ISSUES - Anisa Rizki Titania (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Around 800,000 people die by suicide in a year, or one per 40 seconds. Despite the fact that suicide is a complex phenomenon impacted by personal qualities as well as numerous socioenvironmental factors, it is considered as a avoidable public health problem, and public health methods to suicide prevention are fast gaining traction. Because of its vast impact, media might be considered to have a "dual-edged" polarity when it comes to mental health. It has the potential to increase mental health awareness, education, and development of treatment and service, but it also has the potential to undermine awareness, disseminate misinformation, and stigmatize mental health. This article is made by reviewing and evaluating several literatures that discusses media coverage amd public response through social media regarding the suicide of a number of celebrities and their relationship to people's mental health. The literature used is limited to articles published between 2017 – 2021. Prior research on the public's perceptions of celebrity suicide has primarily concentrated on the negative consequences, sometimes recognized as "copycat suicide" in other words "Werther effect" The positive consequences occurred when there was media coverage of a celebrity who committed suicide primarily due to mental health issue in the preceding month, the number of persons who consulted a psychiatrist increased. Increasing 'mental health awareness' on depression and suicide may help people cope with the impact of celebrity suicide news while also making it easier to get help. Inadequate mental health knowledge about depression therapy and suicide prevention may raise the likelihood of negative psychological consequences and lower the desire to seek help among those who are disturbed by such news. Keywords: celebrity, suicide, response